Galectin‐1 production is elevated in hypertrophic scar. Issue 1 (26th October 2020) - Kirkpatrick, Liam D.; Shupp, Jeffrey W.; Smith, Robert D.; Alkhalil, Abdulnaser; Moffatt, Lauren T.; Carney, Bonnie C.
Abstract: Upon healing, burn wounds often leave hypertrophic scars (HTSs) marked by excess collagen deposition, dermal and epidermal thickening, hypervascularity, and an increased density of fibroblasts. The Galectins, a family of lectins with a conserved carbohydrate recognition domain, function intracellularly and extracellularly to mediate a multitude of biological processes including inflammatory responses, angiogenesis, cell migration and differentiation, and cell‐ECM adhesion. Galectin‐1 (Gal‐1) has been associated with several fibrotic diseases and can induce keratinocyte and fibroblast proliferation, migration, and differentiation into fibroproliferative myofibroblasts. In this study, Gal‐1 expression was assessed in human and porcine HTS. In a microarray, galectins 1, 4, and 12 were upregulated in pig HTS compared to normal skin (fold change = +3.58, +6.11, and +3.03, FDR <0.01). Confirmatory qRT‐PCR demonstrated significant upregulation of Galectin‐1 (LGALS1) transcription in HTS in both human and porcine tissues (fold change = +7.78 and +7.90, P <.05). In pig HTS, this upregulation was maintained throughout scar development and remodeling. Immunofluorescent staining of Gal‐1 in human and porcine HTS showed significantly increased fluorescence (202.5 ± 58.2 vs 35.2 ± 21.0, P <.05 and 276.1 ± 12.7 vs 69.7 ± 25.9, P <.01) compared to normal skin and co‐localization with smooth muscle actin‐expressing myofibroblasts. A strong positive correlation ( R = .948) was observed between LGALS1 and Collagen type 1 alpha 1 mRNA expression. Gal‐1 is overexpressed in HTS at the mRNA and protein levels and may have a role in the development of scar phenotypes due to fibroblast over‐proliferation, collagen secretion, and dermal thickening. The role of galectins shows promise for future study and may lead to the development of a pharmacotherapy for treatment of HTS.